The Tragic Equation: Semiotics of Myth in Ted Hughes' Shakespeare - Brlek, Tomislav (Array, 2001)
In Shakespeare and the Goddess of Complete Being (1992) Ted Hughes reads the latter half of Shakespeare's work as a series of variations on a basic structural model. The plays are analysed as formal transformations of the generative matrix expounded in the two contrastive and complementary narrative poems, Venus and Adonis and The Rape of Lucrece, based respectively on two mythical stories. This paper tries to argue that placing this study in the theoretical context(s) and referential framework(s) within which it methodologically aims to situate itself and identifying the critical tenets underpinning it would have prevented the distortive misprisons and ill-judged critical pronouncements it has occasioned. A summary exposition of Hughes' approach in terms of a critical delineating of the limitations of his hermeneutical procedure would also be an indication of the general value or otherwise of this method as demonstrated in its particular applications.